Documenting Geographically and Contextually Diverse Language Data Sources - Angelina McMillan-Major; Francesco De Toni; Zaid Alyafeai; Stella Biderman; Kimbo Chen; Gérard Dupont; Hady Elsahar; Chris Emezue; Alham Fikri Aji; Suzana Ilić; Nurulaqilla Khamis; Colin Leong; et al. (Northern European Journal of Language Technology)
Contemporary large-scale data collection efforts have prioritized the amount of data collected to improve large language models (LLM). This quantitative approach has resulted in concerns for the rights of data subjects represented in data collections. This concern is exacerbated by a lack of documentation and analysis tools, making it difficult to interrogate these collections. Mindful of these pitfalls, we present a methodology for documentation-first, human-centered data collection. We apply this approach in an effort to train a multilingual LLM. We identify a geographically diverse set of target language groups (Arabic varieties, Basque, Chinese varieties, Catalan, English, French, Indic languages, Indonesian, Niger-Congo languages, Portuguese, Spanish, and Vietnamese, as well as programming languages) for which to collect metadata on potential data sources. We structure this effort by developing an online catalogue in English as a tool for gathering metadata through public hackathons. We present our tool and analyses of the resulting resource metadata, including distributions over languages, regions, and resource types, and discuss our lessons learned.